Discurso ante la Junta de Gobernadores, 30 de septiembre de 1968 - McNamara, Robert S. (World Bank, Washington, DC, 2017)
In his first public speech as President of the World Bank, Robert S. McNamara stressed that the Bank faced the question of what action the Bank, as a development organization, needs to take to overcome the recent mood of frustration and failure among developing countries and donors. He noted that Lester Pearson will lead an independent commission on the state of development aid. In the meantime, McNamara vowed that the Bank can and will act, and it will provide leadership in development planning. He proposed that the Bank Group double lending over the next five years, directed at developing national economies, stimulating growth, and aiding the poorest nations which need the most help. Some of this effort will be funded by a dramatic increase in Bank borrowing. Additionally, he note the need for more international representation among the Bank’s staff to really be an International Bank. He called for changes in resource allocation to geographic areas and economic sectors. Aid to the regions of Latin America and Africa will rise relative to South Asia. He advocated increased focus to Education and Agriculture. He called for new initiatives to control population growth. He proposed three courses of action. First, make it clear to developing countries how the rapid growth of the population slows down their development potential. Second, look for opportunities to fund facilities for its members to carry out their programs of family planning. Third, join forces with others in research programs to determine the methods of the most effective family planning and national administration of population control programs.